2015
DOI: 10.1063/1.4922605
|View full text |Cite
|
Sign up to set email alerts
|

Versatile atomic force microscopy setup combined with micro-focused X-ray beam

Abstract: Micro-focused X-ray beams produced by third generation synchrotron sources offer new perspective of studying strains and processes at nanoscale. Atomic force microscope setup combined with a micro-focused synchrotron beam allows precise positioning and nanomanipulation of nanostructures under illumination. In this paper, we report on integration of a portable commercial atomic force microscope setup into a hard X-ray synchrotron beamline. Details of design, sample alignment procedure, and performance of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Another decisive advantage of GISAXS measurements arises from the basic scattering geometry shown schematically in Figure 1 . The geometry comprises the necessary degrees of freedom orthogonal to the beam direction and therefore allows for combining the experimental setup with diverse deposition applications for thin films and/or with complementary measuring methods such as ellipsometry, spectroscopy or atomic force microscopy (AFM) [ 134 , 139 , 143 , 144 , 145 ].…”
Section: Combining Grazing Incidence X-ray Scattering and Sputter mentioning
confidence: 99%
“…Another decisive advantage of GISAXS measurements arises from the basic scattering geometry shown schematically in Figure 1 . The geometry comprises the necessary degrees of freedom orthogonal to the beam direction and therefore allows for combining the experimental setup with diverse deposition applications for thin films and/or with complementary measuring methods such as ellipsometry, spectroscopy or atomic force microscopy (AFM) [ 134 , 139 , 143 , 144 , 145 ].…”
Section: Combining Grazing Incidence X-ray Scattering and Sputter mentioning
confidence: 99%
“…Scanning probe microscopy can supplement X-ray measurements by providing local structural information in real space. Inspired by this potential, several atomic force microscopes (AFM) [4][5][6][7][8][9] and scanning tunneling microscopes (STM) [10][11][12][13][14] have been installed on beamline end stations. In the AFM studies, it was shown that the AFM tip can be used to align the X-ray beam with features of interest [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these limitations, groups around the world have been developing instruments that combine synchrotron radiation with the high spatial resolution of different SPM variants (Okuda et al, 2005;Saito et al, 2006;Scheler et al, 2009;Rose & Freeland, 2010a;Fauquet et al, 2011;Pilet et al, 2012;Chan et al, 2013;Suzuki, 2015;Slobodskyy et al, 2015). Recently, synchrotron X-ray scanning tunneling microscopy (SX-STM) showed the capability to obtain elemental contrast with a lateral spatial resolution of only 2 nm and sensitivity at the limit of single-atomic height (Shirato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%